Primary aldosteronism: An underdiagnosed cause of hypertension: Primary aldosteronism: An underdiagnosed cause of hypertension (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Primary aldosteronism (PA), the most common form of secondary hypertension, can be either surgically cured or treated with targeted pharmacotherapy. PA is frequently undiagnosed and untreated, leading to aldosterone-specific cardiovascular morbidity and nephrotoxicity. Thus, clinicians should perform case detection testing for PA at least once in suspected patients with hypertension. We report a case of a young man presented with hypertension and recurrent hypokalemia. This case highlights the need for clinicians to orient themselves with the clinical and biochemical features of PA to avoid delays in diagnosis and specific treatment of PA to reduce morbidity and mortality.J Assoc Clin Endocrinol Diabetol Bangladesh, July 2023; 2 (2): 79-81